The instrument of the push stroke technique skill in table tennis: validity and reliability - Jeki Haryanto; Naluri Denay (Journal of Educational and Learning Studies, 2021)
The test is a very important data collection tool to assess the abilities possessed by an athlete, the push push skill test in table tennis is not yet available so that coaches and martial arts athletes evaluate the performance of their athletes. This study aims to find out the validity and reliability of the push-punch technique skill test instrument in table tennis. The stages that will be carried out in this research are that the researcher will design the test, after the test is successfully made, the next step is to validate the test and test the reliability of the test. The population in this study were all deepening table tennis students, while the sampling technique used was saturated sampling so that the entire population of 32 people was used as a sample. The results showed that the validity of this test was in the very good category and the reliability of this test was in the high category, so it is hoped that this test can be used by coaches to evaluate the skills of their athletes.